2008 IEEE International Conference on Computer Design 2008
DOI: 10.1109/iccd.2008.4751854
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of buffer sizing for Network-on-Chips under multimedia traffic

Abstract: Designing appropriate buffer sizes for routers within Network-on-Chip (NoC) so as to minimize the power while preserving the required performance in the presence of self-similar traffic has been considered a challenging problem in the literature. A few analytical studies carried out in NoC modeling have been adopted assumptions such as exponentiallydistributed packet inter-arrivals, and conclusions reached under such assumptions may be inappropriate in the presence of self-similar traffic. Through mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, wormhole routing is more suitable for NoC as it requires less implementation cost. Because of the differences between wormhole and storeand-forward/virtual-cut-through, the methods in [6] and [22] cannot be directly used to customize the buffer resources for wormhole NoC.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, wormhole routing is more suitable for NoC as it requires less implementation cost. Because of the differences between wormhole and storeand-forward/virtual-cut-through, the methods in [6] and [22] cannot be directly used to customize the buffer resources for wormhole NoC.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [6,22] propose buffer allocation methods for store-and-forward or virtual-cut-through [23] NoC, respectively. However, wormhole routing is more suitable for NoC as it requires less implementation cost.…”
Section: Related Workmentioning
confidence: 99%
“…[19][20] suggested that the specific application had a significant relationship with the Hurst parameter. [21] demonstrated that increasing channel service rate of NoC reduced self-similarity degree. Although the development procedure of the traffic modeling in NoC is similar to it in the computer networks, it is impractical to blindly reuse features of application-specific traffic models in computer networks.…”
Section: Application-specific Traffic Models For Nocmentioning
confidence: 99%